Thatcherism - Holmes, Martin. author. aut Link
VIII, 174 p.
Keywords: This book examines the pace of change and the nature of the Thatcherite revolution, 1983-87. It draws on 30 interviews with ministers and officials and offers a critique of existing theories of Thatcherism. The author assesses the progress of, opposition to and future of policy.